New frontiers in mining complex patterns : 6th International Workshop, NFMCP 2017, held in conjunction with ECML-PKDD 2017, Skopje, Macedonia, September 18-22, 2017, Revised selected papers /: 6th International Workshop, NFMCP 2017, held in conjunction with ECML-PKDD 2017, Skopje, Macedonia, September 18-22, 2017, Revised selected papers. (2018) - Unknown
No abstract available